Evidence-Based Massage Therapy - Lebert, Richard (Open textbook library., 2018)
Massage Therapists want to help people, and part of our approach requires having a clear message of who we are and the value we offer. Adopting an evidence-based conceptual framework offers a solution, as it can provide a cohesive message of our nature and value. This clinical practice handbook will prove essential to massage therapists, physical therapists, chiropractors, medical doctors, psychologists and other health professionals who care for people with musculoskeletal pain. It will be continuously updated as new research becomes available.